PENGARUH PENGGUNAANMODEL INKUIRI TERHADAPHASIL BELAJAR IPA DI SEKOLAH DASARPONTIANAK UTARA - Deby Sandra; Rosnita Rosnita; Mastar Arsan (Universitas Tanjungpura, 2018)
Abstract This research aims to understand the influence of the use of Inquiry Model on the learning outcomes of natural science student class in Elementary School 41 Pontianak.Population in this research is all students grade V academic year 2017 / 2018 which consisted of 64 people.Sample in this research were students grade 5 which consisted of 64 people consisting of 32 the VB and 32 the V A ( class eksperimen).Instrument gatherer data of student learning the test results obtained from pre test and post test. The results of the study , obtained the average test results final grade control 63,68 and the average test results final grade 74,39 experiments obtained thitung of 3,3445 and ttabel with α = 5% and dk = 32 as much as , which means thitung (3,3445) > ttabel (1,9993), thus then Ha accepted .Of reckoning as effect size (ES), obtained ice as much as 0,87 ( criteria high ) .This means that learning with the use of Inquiry models difference that high evaluation learning outcomes from the classroom v in elementary school 41 Pontianak. Keyword : Inquiri Model, Study Result, Natural Science